Screening of rice genotypes for salt tolerance by physiological and biochemical characters - Bhowmik, Uttam; Kibria, Mohammad Golam; Rhaman, Mohammad Saidur; Murata, Yoshiyuki; Hoque, Md. Anamul (Plant Science Today, 2021)
Crop production is unexpectedly hampered by different abiotic stresses. Salinity is one of the leading stresses, which snappishly hampers plant developmental progression. Local rice landraces exhibit noticeable salt tolerance as well as high yield. However, research is scarce about the physio-biochemical responses of local landraces and modern cultivar under saline conditions. Therefore, the present experiment was designed to reveal the physio-biochemical responses of local landraces and modern cultivar under salinity stress. Five landraces (Jotai, Icheburogolghor, Morishal, Chapail, Kumro buro) and two modern cultivars (BR23 and BRRI dhan41) were subjected to 0, 20, 40, 60 and 80 mM NaCl treatment. The effects of salt stress on morphological parameters, proline contents, and activities of antioxidant enzymes were assessed. Salt stress reduces the morphological parameters of all tested cultivars. The Morishal and BRRI dhan41 exhibited higher growth of plant and physiological parameters than other cultivars under the highest salinity. The catalase (CAT) and ascorbate peroxidase (APX), exhibited a significant increase whereas peroxidase (POX) activity significantly declined in all the cultivars under salinity stress. Morishal and BRRI dhan41 showed the highest proline content under the maximum saline condition. These results suggest that the high tolerant landrace and modern cultivars were Morishal and BRRI dhan41 respectively. These results also suggest that Morishal and BRRI dhan41 exhibited high tolerance to salinity by enhancing proline content and antioxidant enzyme activities.